Reducing Copper (II) Ions from Aqueous Solutions Using Ficus-Activated Carbon - Abu Jamra, Muhammad Muammar; Abed , Kaled Ali; Al-Nakua, Saleh Al-Hamali (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Heavy metals are inherent natural elements in the earth’s crust and can be byproducts of industrial activities such as petrochemicals and other manufacturing processes. In this study, the adsorption of heavy metal ions Cu(II) from wastewater using Ficus Activated Carbon (FAC) and the relationship between different adsorption coefficients in the removal of heavy metal ions Cu(II) was examined. The analysis was done by using a spectrophotometer device (ONDA V-10 PLUS). The optimum conditions were a contacting time of 100 minutes at 200 rpm, with 0.4 g of FAC per 35 ml of solution, a particle size of 0.2mm, pH =6, and a temperature of 25 °C. The adsorption capacity for heavy metal ions increased with increasing temperature, pH, contact time, and concentration of heavy metal ions, but decreased with increasing particle size. The adsorption processes are therefore spontaneous thermal desorption processes, and the results demonstrated a good agreement with pseudo-second-order kinetics. The adsorbent prepared in the laboratory (FAC) was placed in a high-temperature 200 oC oven and then activated with hydrogen peroxide acid (H2O2), thus having higher removal rates. In addition, 90% of the heavy metal ions were significantly removed and made the solution the permitted values. The results show that FAC can be used as a green for the adsorption of heavy metals from water.